O Núcleo UHUU de pesquisa da performance: inter-ação e inter-locus-ação - Simões, Rosa Maria Araújo [UNESP] (My University, 2012)
The 'Performance Research UHUU Centre: interarts and multimedia' of Unesp Bauru is a possibility, among countless attempts, to break off the distance between the show and the audience, imposed by the classic dramaturgy. Seeking for re-establishing the vital energy dialogue between the artist and his public, the performance art is focused, which, opposed to the theatre orthodox conceptions (which presuppose a highlighted place to the transmitter regarding the receiver), places the public as the interlocutor and even as the message co-author. The aim of this work is to show that the UHUU Centre focus on works such as researches and productions in partnership with the Marcio Pizarro and the processes-researches-actions in partnership with the Interarts CNPq Research Group: interartistic processes and systems and performance studies.
Keywords: Performance art; UHUU Centre